Oral Colonization by Different Candida Species: First Comparative Study between Denture and Nondenture Wearers in Tunisia - Benyounes, Oussama; Bekri, Sana; Belgacem, Sameh; Labidi, Amel; Khemis, Mehdi; Mansour, Lamia (European Journal of Dentistry, 2024)
Objective This study aimed to compare different Candida species present in patients with and without removable dentures to identify alterations in biofilm composition following denture wear within a Tunisian population.Materials and Methods A cross-sectional study was conducted, comprising a group of patients wearing removable dentures (test group) and a control group without dentures. In the test group, two mycological samples were obtained: one from the prosthetic intaglio and another from the osteomucosal area bearing the denture. For the control group, mycological samples were collected from the oral mucosa. The collected swabs were cultured on CHROMagar Candida medium, and yeast counts were quantified as colony forming units (CFUs). Candida species were identified through chromogenic analysis.Statistical Analysis The normality of quantitative variables was evaluated using the Kolmogorov–Smirnov's test. To compare means and ranks between the test and control groups, the independent samples t-test and the Mann–Whitney's U test were employed, respectively. Qualitative variables were compared using Fisher's exact test. Statistical significance was determined at a critical uncertainty value of p < 0.05.Results A total of 150 participants were involved in this study, with 75 patients in each group. Wearing an acrylic removable denture was found to increase the number of detected Candida species (p < 0.001) and significantly increases the overall growth of Candida spp. (p = 0.001). Specifically, the numbers of CFUs of Candida tropicalis and Candida glabrata were elevated in denture wearers (p < 0.001).Conclusion Findings stemming from this study indicate that removable dentures promote the growth of Candida species. This can be a predisposing factor for Candida-associated denture stomatitis in cases of poor oral hygiene or compromised immunity. Therefore, it is imperative to emphasize the fabrication of high-quality dentures and the implementation of rigorous postdenture maintenance protocols to prevent or limit Candida infection.
Keywords: Candida albicans; Candida tropicalis; Candida glabrata; Candida krusei; removable dentures